2013
DOI: 10.1111/ejh.12131
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow cell transcripts from Fanconi anaemia patients reveal in vivo alterations in mitochondrial, redox and DNA repair pathways

Abstract: Fanconi anaemia (FA) is a genetic cancer predisposition disorder associated with cytogenetic instability, bone marrow failure and a pleiotropic cellular phenotype, including low thresholds of responses to oxidative stress, cross-linking agents and selected cytokines. This study was aimed at defining the scope of abnormalities in gene expression using the publicly available FA Transcriptome Consortium (FTC) database (Gene Expression Omnibus, 2009 and publicly available as GSE16334). We evaluated the data set th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…Three independent studies of MDF in FA cell lines of different genetic subtypes provided evidence for abnormal ultrastructure and function of mitochondria in FA cells [5759]. Our recent report on bone marrow cell transcripts from FA patients revealed downregulation of genes involved in mitochondrial functions, antioxidant activities, heat shock proteins, and chelating proteins [60]. Thus, the role in the FA phenotype of OS/MDF may be considered well established and awaits consequent interventions in clinical management, in view of preventing or delaying disease progression.…”
Section: Genetic Diseasesmentioning
confidence: 99%
“…Three independent studies of MDF in FA cell lines of different genetic subtypes provided evidence for abnormal ultrastructure and function of mitochondria in FA cells [5759]. Our recent report on bone marrow cell transcripts from FA patients revealed downregulation of genes involved in mitochondrial functions, antioxidant activities, heat shock proteins, and chelating proteins [60]. Thus, the role in the FA phenotype of OS/MDF may be considered well established and awaits consequent interventions in clinical management, in view of preventing or delaying disease progression.…”
Section: Genetic Diseasesmentioning
confidence: 99%
“…A number of additional DNA repair factors associate with FA proteins [40]. Recent study of transcripts from bone marrow cells revealed that FA patients have deficiencies in mitochondrial, redox and DNA repair pathways [41,42]. Another DNA-repair deficient disease is Ataxia Telangiectasia (AT) that is caused by mutations on the ATM gene [43].…”
Section: Dna-repair Factors and Mitochondrial Functionsmentioning
confidence: 99%
“…Since FA proteins have been shown to regulate oxidative stress and mitochondrion respiration complex enzymes91213161718, and since mitochondrial Fancd2-interactors show the highest enrichment score in our proteomic analysis (Fig. 2 above), we decided to study the link between FA and the mitochondrion further.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies show that FA cells exhibit abnormalities in mitochondrial metabolism, Ca 2 + homeostasis, and gene expression91011. Additional studies revealed mitochondrion defects in FA patients and mice12131415.…”
mentioning
confidence: 99%